Nanomaterials: brief review of policy frameworks in the US and Europe and recommendations from an occupational and environmental perspective - Sass, Jennifer; Musu, Tony; Burns, Kathleen; Illuminato, Ian (European Journal of Oncology and Environmental Health, 2008)
Nanomaterials are already incorporated into over 800 consumer products, according to self-disclosures by industry in their consumer advertising. Increasing numbers of toxicological studies have reported on the toxicity of different nanomaterials, suggesting a potential public and occupational health risk associated with exposure to at least some classes of nanomaterials. At this time, the US is primarily relying on a voluntary corporate stewardship to provide oversight of nanomaterials. European Union leaders are voicing the need for precaution although no significant protective actions have been taken thus far. This manuscript provides a brief review of relevant chemical policies, and identifies the weaknesses and loopholes in some of the US and European Union chemical policies that are relevant to nanomaterials. The long-term goal of this project is to support effective health-protective policies for managing hazardous chemicals.